Delivering the Diabetes Remission Clinical Trial (DiRECT) in primary care: Experiences of healthcare professionals. Issue 3 (15th December 2021) - Rehackova, Lucia; Taylor, Roy; Lean, Mike; Barnes, Alison; McCombie, Louise; Thom, George; Brosnahan, Naomi; Leslie, Wilma S.; Sniehotta, Falko F.
Abstract: Objective: The Diabetes Remission Clinical Trial (DiRECT) used a formula total diet replacement programme followed by structured weight loss maintenance to induce and sustain weight loss and remission of type 2 diabetes (T2D) in 36% of participants after 2 years. Nurses and dietitians delivering DiRECT in 22 primary care practices in Tyneside and Scotland provided behavioural support to participants. Participant experiences with DiRECT highlighted the key role of support by healthcare professionals (HCPs). We evaluated HCPs' experiences with DiRECT. Research design and methods: Healthcare professionals delivering DiRECT were interviewed at 12 months, while general practices (GPs) were sent an implementation questionnaire. The interviews were analysed thematically. The questionnaires were analysed using frequencies and a narrative synthesis. Results: Healthcare professionals representing 11 of 22 intervention practices were interviewed and 10 of 22 GPs completed questionnaires. HCPs' initial concerns over perceived potential negative intervention effects, particularly withdrawing anti‐diabetes and anti‐hypertensive medications, were barriers to engagement. Trust of HCPs towards the research team and perceived credibility of the study facilitated engagement and adoption. Ongoing support by research dietitians was key to the management of participants. Involvement in DiRECT inspired more focus on behaviour modification in the treatment of other people living with T2D in routine practice. Conclusions: Diabetes Remission Clinical Trial was considered highly appropriate for the management of T2D in primary care when supported by trained dietitians. Addressing limitations, including varying training needs of HCPs may improve intervention scale‐up and tailoring to clinical contexts.